Preoperative sonographic diagnosis of sliding appendiceal inguinal hernia - Akfirat, M; Kazez, A; Serhatlioglu, S (John Wiley & Sons Inc, 1999)
Rarely, the appendix forms the sliding component of an inguinal hernia. We report the case of a 2-month-old boy who was preoperatively diagnosed with sliding appendiceal inguinal hernia by sonographic examination. To our knowledge, this is the first report in the literature of the preoperative sonographic diagnosis of a sliding appendiceal inguinal hernia. (C) 1999 John Wiley & Sons, Inc.
VIth International Congress of the Mediterranean-and-African-Society-of-Ultrasound -- APR 25-28, 1998 -- KUSADASI, TURKEY
Keywords: sliding inguinal hernia; appendix; ultrasonography; infant